2011
DOI: 10.1093/infdis/jir328
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Immunization Against H5N1: A Randomized Trial Evaluating Homologous and Cross-Reactive Immune Responses to AS03A-Adjuvanted Vaccination in Adults

Abstract: Background. Accelerated immunization schedules may help gain early control of influenza pandemics. We investigated different schedules of an AS03A-adjuvanted H5N1 vaccine.Methods. This phase II, open-label, 6-month study randomized participants (aged 18–64 years) to 2 vaccine doses administered 21 (standard schedule), 14, or 7 days apart, or on the same day. Coprimary end points were that the lower limit of the 98.75% confidence interval 14 days after the last dose must be (1) >40% for seroconversion rate (SCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Both of AS03-adjuvanted CC-H5N1 formulations were immunogenic for the homologous and drift variant A/Vietnam/1194/2004 strains in terms of HI and NAbs and met CBER criteria for immunogenicity of pandemic vaccines for both strains. The potential for cross-clade immunogenicity is fundamental to priming a population in a prepandemic or early pandemic setting, providing priming or protection until a pandemic strain-matched vaccine becomes available [ 10 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both of AS03-adjuvanted CC-H5N1 formulations were immunogenic for the homologous and drift variant A/Vietnam/1194/2004 strains in terms of HI and NAbs and met CBER criteria for immunogenicity of pandemic vaccines for both strains. The potential for cross-clade immunogenicity is fundamental to priming a population in a prepandemic or early pandemic setting, providing priming or protection until a pandemic strain-matched vaccine becomes available [ 10 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that vaccines formulated with AS03 are highly immunogenic against H5N1 avian strains and the human pandemic influenza H1N1 strain in elderly and non-elderly adults. [6][7][8][9][10] A community-based casecontrol study of the MF59-adjuvanted trivalent seasonal vaccine has also shown benefit in the elderly versus a nonadjuvanted vaccine. 11 Thus, adjuvanted vaccines provide a potential approach to reduce the incidence and severity of influenza in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have considered a longer time-lag (four weeks) 26 , which would lead to even lower impact on reducing attack rates. However, a recent randomized trial of H5N1 adjuvanted vaccine suggests that accelerated immunization schedules with a short time-lag (7 or 14 days) between the first and second doses may be effective in enhancing vaccine efficacy and help gain early control of influenza pandemics 27 . Our simulations corroborate these effects in the population, demonstrating that as the time-lag between vaccine doses reduces, the impact of vaccination becomes more pronounced on reducing attack rates.…”
Section: Discussionmentioning
confidence: 99%